Vitamin D metabolism and regulation in pediatric MSCs. Issue 164 (November 2016) - Ruggiero, B.; Padwa, B.L.; Christoph, K.M.; Zhou, S.; Glowacki, J.
Highlights: Pediatric MSCs showed constitutive expression of CYP27B1 and other vitamin D-related genes. There was greater expression of vitamin D-related genes in MSCs from boys than girls. Those gender differences had not been seen in MSCs from adults. Vitamin D-related genes were upregulated by in vitro treatment with 25(OH)D3 and with 17β-estradiol. Expression and regulation of vitamin D-related genes in pediatric hMSCs reinforces an autocrine/paracrine role for vitamin D in hMSCs. Abstract: Vitamin D is crucial for mineral homeostasis and contributes to bone metabolism by inducing osteoblast differentiation of marrow stromal cells (MSCs). We recently reported that MSCs from adults demonstrate 1α-hydroxylase activity in vitro and express vitamin D-related genes; this raises a possible autocrine/paracrine role for D activation in pre-osteoblasts. In this studies, we tested the hypotheses that pediatric MSCs have 1α-hydroxylase activity and express vitamin D-related genes. With IRB approval, we isolated MSCs from discarded excess iliac marrow graft from 6 male and 6 female subjects (age 8–12 years) undergoing alveolar cleft repair. 1α-hydroxylation of substrate 25(OH)D3 was measured by ELISA for 1α, 25(OH)2 D. RT-PCR was used for gene expression. Pediatric MSCs showed a range of 1α-hydroxylase activity in vitro . There was constitutive expression of vitamin D receptor (VDR), megalin, d -hydroxylases (CYP27B1, CYP27A1, CYP2R1, and CYP24A1), and estrogen receptor (ER). There was 2.6-fold greater expression of CYP27B1 and 3.5-fold greater expression of CYP24A1 in MSCs from boys compared with girls. There was 2.4-fold greater expression of ERα and 3.2-fold greater expression of megalin in MSCs from boys. In preliminary studies, treatment of female pediatric MSCs with 10 nM 17β-estradiol resulted in upregulation of CYP27B1 and CYP24A1, as well as VDR, megalin, ERα, and ERβ. Treatment with 25(OH)D3 upregulated CYP27B1, VDR, and ERα. Expression and regulation of vitamin D related genes in pediatric hMSCs reinforces an autocrine/paracrine role for vitamin D in hMSCs. Finding striking gender differences in MSCs from children was not seen with MSCs from adults and adds insight to the metabolic environment of bone and presents a research approach for investigating and optimizing pediatric bone health.